Agronomic characterization of sweet potato accessions - Vargas, Pablo Forlan [UNESP]; Godoy, Dumon Ramiro Zanetti [UNESP]; De Almeida, Luis Carlos Ferreira [UNESP]; Castoldi, Renata (Lepidus Tecnologia, 2017)
The agronomic characterization of a genotype set is one of the basic steps to start a breeding program, as action strategies to search for new cultivars are defined through the knowledge of these characteristics. Thus, the aim of this study was to rescue and assess agronomic performance in accessions collected in traditional communities. Sweet potatoes were collected among quilombos, indigenous villages, native populations and small farmers from Vale do Ribeira. The study was conducted at UNESP, Registro Campus, from February/2013 to August/2014. The experiment was set in a randomized blocks design with 95 accessions, two commercial cultivars, Brazlândia Branca and Brazlândia Roxa (controls), with three repetitions. Total commercial roots production, percentage of commercial roots production, total roots dry matter production, roots dry matter percentage, fresh branches production, total dry matter production in branches and dry matter percentage in branches were assessed. Accessions VR13-62, VR13-61, VR13-44, VR13-11 and VR13-14 demonstrated characteristics of roots for consumption and VR13-11 and VR13-14 for industry consumption due to the high dry matter percentage obtained per hectare; VR13-35, VR13-87 and VR13-22 are adequate for animal feed purposes. VR13-11, VR13-22 and VR13-58 accessions can be used for human and animal consumption; VR13-48 was suitable for home and industry consumption; and VR13-4 and VR13-31 was suitable for animal feed and industry consumption.
Keywords: Agronomic performance; Germplasm; Ipomoea batatas; Pre-breeding